Investigation of in vitro and in vivo antioxidant and antidiabetic activities of Pinus halepensis extracts - Najoua Salhi; Abdelhakim Bouyahya; Otman El-Goumari; Meryem El Jemly; Ilhame Bourais; Amina Zellou; Yahya Cherrah; My El Abbes Faouzi (Shahrekord University of Medical Sciences, 2021)
Introduction: Pinus halepensis is a medicinal plant used in traditional medicine for treatment of various pathologies including diabetes. The objective of this study is to perform a phytochemical study and to evaluate the antioxidant and antidiabetic activities of extracts of the bark of P. halepensis. Methods: Total polyphenols, flavonoids and tannins were determined by the Folin Ciocalteu method, aluminum trichloride reagent (AlCl3) and vanillin assay. Evaluation of the antioxidant activity was carried out using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2'-azinobis- (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and ferric reducing agent (ferric reducing). The antidiabetic activity was first revealed by enzymatic inhibition tests through measuring the residual activities of α-amylase and α-glucosidase, and then, by oral tolerance tests of glucose and starch in male Wistar rats. To verify the safety of plant extracts, acute oral toxicity was determined. Results: The phytochemical analysis showed that the extracts of P. halepensis were rich in phenolic compounds. The anti-oxidation activity tests revealed a significant reducing power towards the radicals tested. In addition, P. halepensis inhibited the enzymes involved in diabetes (α-amylase and α-glucosidase) at very low concentrations. These effects were verified in the in vivo approach, in particular by using the starch tolerance test. Conclusion: P. halepensis extracts showed remarkable antioxidant and antidiabetic effects. However, further investigations are necessary to identify the main compounds of P. halepensis and to evaluate their antioxidant and antidiabetic effects.